2002
DOI: 10.1210/endo.143.5.8804
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ghrelin in the Regulation of Vasopressin Release in Conscious Rats

Abstract: GH secretagogue (GHS) is a small, synthetic compound that has the potential to stimulate GH release via its specific receptors (GHS-R). Ghrelin is a novel 28-amino acid peptide recently isolated from human and rat stomach, and it is thought to be the endogenous ligand for GHS-R. Ghrelin has a variety of physiological functions such as the stimulation of GH release or the increase of food intake by activating NPY neurons. In the present study, we investigated the effects of ghrelin on AVP release in conscious r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
19
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 27 publications
4
19
0
1
Order By: Relevance
“…the reason for this may be that GhRp-2 might have a different effect on AVp secretion independent of osmolality and hemodynamic factors, unlike ghrelin, probably because GhRp-2 is an exogenous ligand that binds the GhS receptor, while ghrelin is an endogenous ligand that binds the GhS receptor [2]. this difference supports the notion that, for Acth secretion, GhRp-2 acts via cRF [7], while ghrelin acts via AVp [12], and ghrelin stimulates secretion of gastric juice with gastrin, whereas GhRp-2 has no such effects [23]. Moreover, AVp levels increase significantly with the itt [17][18][19].…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…the reason for this may be that GhRp-2 might have a different effect on AVp secretion independent of osmolality and hemodynamic factors, unlike ghrelin, probably because GhRp-2 is an exogenous ligand that binds the GhS receptor, while ghrelin is an endogenous ligand that binds the GhS receptor [2]. this difference supports the notion that, for Acth secretion, GhRp-2 acts via cRF [7], while ghrelin acts via AVp [12], and ghrelin stimulates secretion of gastric juice with gastrin, whereas GhRp-2 has no such effects [23]. Moreover, AVp levels increase significantly with the itt [17][18][19].…”
Section: Discussionsupporting
confidence: 53%
“…secreted from the stomach and circulates in the bloodstream under fasting conditions [5], and the GhSs have a stimulating effect not only on Acth via cRh in animals [6,7] and humans [4,[8][9][10], but also on arginine vasopressin (AVp) in animals [6,11,12] and humans [9,10]. interestingly, ghrelin plays a stimulatory role in AVp release mediated by neuropeptide y (npy) neurons in rat [11,12].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, native AG stimulates AVP release from rat posterior pituitary gland, probably via an indirect action mediated by NPY neurons (Ishizaki et al 2002, Wren et al 2002. Notably, AG-induced ACTH release has also been suggested to be mediated by the AG action on AVP secretion, because the AG-induced AVP rise precedes the increase in ACTH and cortisol levels in response to AG injection in healthy men (Coiro et al 2005).…”
Section: Posterior Pituitary Hormonesmentioning
confidence: 98%
“…Furthermore, ICV administration of ghrelin has been shown to increase plasma vasopressin level without a significant change in arterial pressure in conscious rats. 8 It has also been reported that intravenous injection of human ghrelin elicits a decrease in blood pressure without an increase in heart rate (HR) in healthy men. 9 In addition, plasma ghrelin concentration is increased in patients with cachexia associated with chronic heart failure.…”
mentioning
confidence: 99%